2018
DOI: 10.5005/jp-journals-10051-0150
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Acceptance of Dental Implants as a Treatment Modality for Replacement of Missing Teeth among Patients in Aseer Region, Kingdom of Saudi Arabia

Abstract: Aim: The aim of this study was to assess the level, sources of information, awareness, and acceptance of dental implant therapy among dental patients in Aseer region, Kingdom of Saudi Arabia. Materials and methods: Information on demographic variables, level and sources of information, awareness, and acceptance of dental implant therapy as a treatment modality was obtained by self-explanatory survey containing 17 questions. The data were collected at five government dental health centers at Aseer region. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The majority of the participants in this study (70.9%) were interested to know about dental implants, similar to a study done in India (69.9%) [ 10 ]. Though, the percentage of the population interested was less than that of a study done in Saudi Arabia (90.1%) [ 1 ]. This suggests that dental education and training about dental implants are of the utmost importance.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The majority of the participants in this study (70.9%) were interested to know about dental implants, similar to a study done in India (69.9%) [ 10 ]. Though, the percentage of the population interested was less than that of a study done in Saudi Arabia (90.1%) [ 1 ]. This suggests that dental education and training about dental implants are of the utmost importance.…”
Section: Discussionmentioning
confidence: 89%
“…More than one-third of participants (39.6%) thought that the dental implants are fixtures to the jaw bone, which was consistence with Parmita et al (24.5%) [ 11 ] and in disagreement with AlQahtani (56.6%) [ 1 ]. Regarding the need for special care and hygiene, it was found that 27.8% of participants believed that implants needed more care than natural teeth, which was similar to a study conducted by AlQahtani (58.3%) [ 1 ], and Esfahani et al (47.4%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, AlQahtani discussed patient awareness and acceptance of dental implants as a treatment modality for replacement of missing teeth in the Aseer region of Saudi Arabia [ 18 ], while in 2023, Rownaq et al presented the assessment of current knowledge, awareness, and attitudes toward dental implants as a treatment option for replacement of missing teeth in the Riyadh region of Saudi Arabia [ 19 ]. However, there is no published data in the Aseer region of Saudi Arabia covering the conventional prosthetic replacement of missing teeth.…”
Section: Introductionmentioning
confidence: 99%